Ureteroscopic lithotripsy by thulium fiber laser versus holmium laser: A single-center prospective randomized study - Vaddi Chandramohan; P M Siddalinga Swamy; Paidakula Ramakrishna; Soundarya Ganesan; Manas Babu; Hemnath Anandan; Rakesh Panda (Urology Annals, 2023)
Objective: Laser lithotripsy has been the standard of care for lower and mid-ureteric calculi. Thulium fiber laser (TFL) is a new introduction to this field, which has been extensively studied for retrograde intrarenal surgery. We have done a prospective randomized study of ureteroscopic lithotripsy between TFL and holmium: Yttrium-aluminum-garnet (HO: YAG) laser to know the efficacy of stone fragmentation, stone-free rate, and complications. Methodology: A prospective randomized study was done in our hospital from March 2021 to May 2022 on patients planned for ureteroscopic laser lithotripsy. Patients with distal and mid-ureteral stones from 4 mm to 15 mm were included. The laser was used to fragment the stone. All the stones were fragmented from the center to periphery. The setting used was up to 10 W (6–10 Hz, 1J) for TFL and up to 10W for HO: YAG (5–10 Hz, 0.5–1J). Once the stones were fragmented, they were retrieved until complete visual clearance. Demographic data and stone parameters such as stone size, volume, density, laterality, laser usage time, total operative time, and total energy used were recorded. Operative time, lasering time, retropulsion rate, ablation speed, and visibility score were recorded. Results: Each group had 90 randomized patients. Both the groups had similar kinds of patient and stone profiles. The mean operating time was 18.5 ± 1.5 min (95% confidence interval [CI] 16.2–25.6) in the TFL group, which was shorter than the holmium group 31.6 ± 1.2 min (95% CI 18.4–38.5), and it was statistically significant (P = 0.024,). Lasering time was also statistically significant with less lasering time with TFL group 7.4 ± 1.8 min (95% CI 5.2–10.3) versus holmium group 14.8 ± 1.5 min (95% CI 12.3–18.4) (P = 0.011). Laser efficacy and ablation speed were better in the TFL group compared to the HO: YAG group and were statistically significant. The visual score was better in HO: YAG group compared to the TFL group. Conclusion: TFL is more efficacious and faster than Holmium: Yag laser. Complications were similar between the groups. Stone-free rate was also similar between both the groups.